Sacroiliac subluxation in a horse in Colombia (FAVE Sección Ciencias Veterinarias, 2021)
Sacroiliac subluxation is a claudiogenic disease of the hind limbs that can present acutely or chronically. The cause of this pathology is mainly due to slipping, tripping, or falling of the hind limbs, the diagnosis is difficult to make due to the deep anatomical location of the joint, methods such as ultrasound and stress tests among others, are the procedures most used in the diagnosis of sacroiliac subluxation. As it is an alteration that can easily be confused with other pathological conditions of the spine, pelvis and / or the hind limbs, the diagnosis is often made by eliminating other causes of lameness. Conventional treatments are still proposed in the literature, however regenerative therapy is increasingly used as an option for the treatment of sacroiliac joint injuries. This report describes the case of a Creole horse that suffered an acute sacroiliac subluxation on the right side, which was diagnosed with a clinical examination that included percutaneous and transrectal ultrasound and treated with ultrasound-guided infiltrations of corticosteroids and cells of the bone marrow of the sternum without processing. One month after the last therapy, the horse showed an 80% to 90% recovery and resumed controlled physical activity.